Chapter 5.24 The Profession of Research Management and Administration in Romania - Tibor Toró; Dezső Szenkovics; Szilvia Varga (Emerald Publishing Limited, 2023)
Research management and administration (RMA) is a globally emerging field, but it is not yet established in Romania. The chapter analyses what are the formal expectations regarding RMA in the Romanian research system, and how these tasks are resolved on the ground. First, policy documents and informational packages of the major research funding calls are examined. Second, interviews are conducted with research project leaders, who undertook projects in different research organisations (state financed or private universities, state financed research institutions, or private foundations) in Romania. The interviews focussed on the challenges project leaders experienced in the grant seeking and implementation process, and on how they see the institutional and policy environment they work in. In the concluding parts of the chapter, concrete policy recommendations are formulated that could help in resolving the research management related challenges, and in establishing RMA as a profession in the country.
10.1108/978-1-80382-701-820231058; 10.1108/978-1-80382-701-820231058; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262